(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The goal of research is to identify factors influencing the attitudes of high school and university students in Lattakia governorate towards their academic disciplines and their relevance The requirements of the current labor market in the governorate, To achieve the research objective, we analyzed the problem of the incompatibility between higher education outputs, "Tishreen University", and the needs of the labor market. The following was studied in parallel: First, Labor market requirements; based on initial questionnaire distributed to (122) business organizations, and another questionnaire distributed to (142) graduate students. Second: Identifying factors influencing student attitudes toward academic disciplines based on two first two questionnaires. The first was directed to a sample of (2519) high school students and the second to (2382) university students in the first and graduation years. The university students ’attitudes towards their major’s study were measured by using a third questionnaire. The analytical descriptive approach was adopted to characterize variables and analyze relationships among them according to an increasing time-bound analysis, from analyzing factors influencing the attitude toward academic specialization at the high school level up to university capacity, and then graduation from university and the appropriateness of graduate specialization to the requirements of the current labor market, To test the hypotheses, many statistical tests were relied on, including the adequacy of representation test, the difference tests for two independent samples, and the difference test for one sample. The research team reached many results, the most important of which are: The method of recruitment and employment in the public sector had the greatest impact on students’ preferences for university majors. Also, the gender variable had no influence on the orientation to the university specialization. The private sector is more interested than the public sector in professional and technical skills during employment. Based on the results of the research, the research team suggested re-studying the wage system in the public and private sectors in order to be directed to the business market, and to establish the Center for the Development of Administrative Skills in Universities, in addition to the necessity of creating a center for professional guidance and counseling at the pre-university level that acts as a psychological counselor for pre-university students.